Some Properties of Ap Weight Function - Ghimire, Santosh (Journal of the Institute of Engineering, 2017)
In this paper, we briefly discuss the theory of weights and then define A1 and Ap weight functions. Finally we prove some of the properties of Ap weight function. Journal of the Institute of Engineering, 2016, 12(1): 210-213